Ways of managing insurance claims - Iskandarov Abdurasul Mirjalil oglu (THE INNOVATION ECONOMY, 2026)
This article highlights the theoretical and practical aspects of insurance claims management, the interaction of insurance market participants, and effective management methods. Foreign experience has been analyzed and practical recommendations have been developed for Uzbekistan’s insurance companies.